2017
DOI: 10.1007/s00432-017-2471-x
|View full text |Cite
|
Sign up to set email alerts
|

Unmonitored use of herbal medicine by patients with breast cancer: reframing expectations

Abstract: Unmonitored use of herbal medicine by patients with breast cancer is more frequent among those adopting dietary changes for cancer-related goals. Integrative physicians provide evidence-based guidance on the safe and effective use of herbal products, and reframe patient expectations from cancer-related goals to reducing symptoms and improving quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…It is pivotal that the providers' approach acknowledges the value of CAM products if used properly rather than dismissing them in favor of conventional treatments [ 6 ]. This will minimize patients' resistance to disclosing CAM use and will help integrate CAM products and services into conventional treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is pivotal that the providers' approach acknowledges the value of CAM products if used properly rather than dismissing them in favor of conventional treatments [ 6 ]. This will minimize patients' resistance to disclosing CAM use and will help integrate CAM products and services into conventional treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations revealed that the use of herbal medicines, usually as the complementary and alternative treatment, increased dramatically and became popular around the world (Ramos-Remus and Raut, 2008 ; Harris et al, 2012 ; Putthapiban et al, 2017 ). Meanwhile, the safety of herbal medicine and herbal-drug interactions have been highlighted and drawn extensive attention from the medical community (Brazier and Levine, 2003 ; Samuels et al, 2017 ; Singh and Zhao, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of complementary medicines in helping patients endure traditional treatments have already been described (Ludwick et al., 2020; Shalom‐Sharabi et al., 2017), though the methodology of studies on complementary medicines is often weak (Lee, Choi, & Hyun, 2019). Moreover, adverse interactions between complementary medicines and conventional treatment (Velicer & Ulrich, 2008) and the risk of patients delaying or discontinuing conventional treatment have both been seen to be associated with reductions in survival in complementary medicine users (Greenlee et al., 2016; Johnson et al., 2018a; Johnson, Park, Gross, & Yu, 2018b; Samuels, Ben‐Arye, Maimon, & Berger, 2017).…”
Section: Discussionmentioning
confidence: 99%